Impact of Digital Literacy on Informality of MSMES - Sekarranti , Luthfi Tanjung (Future Science, 2025)
The majority of MSMEs stayed informal in many developing countries. This has become a problem because it creates a negative impact on government and business itself. Digital transformation has a transformative impact on formalizing SMEs. This transformation needs entrepreneurs to have a certain level of ability and competence in digital literacy. The main objective of this research is to investigate the impact of higher-level digital literacy of entrepreneurs on MSMEs informality. Informality is defined by three characteristics: bookkeeping, legality, and access to credit on bank. Digital literacy is defined by index constructed using Item Response Theory. Using Propensity Score Matching (PSM) to tackle selection bias and using Ordinary Least Square to analyze the impact of digital literacy, our findings show that digital literacy have a statistically significant and slightly more positive impact on legality than impact on access to credit on bank. In addition, we found that the impact of higher digital literacy on informality is significantly more prominent in western side of Indonesia. However, there is a different impact of higher digital literacy on different sectors of economic activities.